Follicular dynamics and in vivo embryo production in Santa Ines ewes treated with smaller doses of pFSH - Maciel, Giovanna Serpa [UNESP]; Kako Rodriguez, Mariana Garcia [UNESP]; Correia Santos, Victor Jose [UNESP]; Ramirez Uscategui, Ricardo Andres; Nociti, Ricardo Perecin [UNESP]; Maronezi, Marjury Cristina [UNESP]; Oliveira, Clara Slade; Rossi Feliciano, Marcus Antonio [UNESP]; Russiano Vicente, Wilter Ricardo [UNESP]; Fonseca, Jeferson Ferreira da; Franco Oliveira, Maria Emilia [UNESP] (Elsevier B.V., 2019)
To evaluate follicular dynamics, there was assessment of superovulatory response and in vivo embryo production in ewes treated with relatively smaller doses of exogenous pFSH than typically used in combination with a dose of eCG at the beginning of the gonadotropin treatment period. Santa Ines ewes (n = 24) were randomly divided into three groups, based on mg dose of pFSH administered: G200 (n = 8), G133 (n = 8) and G100 (n = 8) in eight decreasing doses at 12-h intervals. All ewes were treated with 300 IU of eCG concomitantly starting with first pFSH administration. Ovulatory follicular dynamics and follicular wall vascularization (FWV) were evaluated using a B-mode and color Doppler ultrasonic machine, respectively. Superovulatory response and embryo production were evaluated 6 days after estrous detection. In the G200 group, the preovulatory follicle size (PFS) were less (P < 0.05), ovulation time later (P < 0.05), and PFS rate greater (P < 0.05); while in the G100 group ovulation rate, and number and percentage of unfertilized eggs were greater (P < 0.05) than in the G133 group (P < 0.05). Number and percentage of viable embryos were greater in the G200 and G100 compared to G133 group (P < 0.05). The dose of 100 mg of FSH was as efficacious as the traditional dose of 200 mg, in combination with a dose of eCG, for superovulatory response and viable embryo production but there was a greater percentage of unfertilized eggs with this treatment.
Keywords: Superovulation; Ovulatory follicular wave; Follicular wall vascularization; Apoptotic embryonic cells; Ovine